Pyruvate Kinase M2 and Cancer: The Role of PKM2 in Promoting Tumorigenesis - Zahra, Kulsoom; Dey, Tulika; Ashish,; Mishra, Surendra Pratap; Pandey, Uma (Frontiers in Oncology, 2020)
Pyruvate kinase plays a vital role in regulating cell metabolism. It catalyzes the rate-limiting step of glycolysis, the conversion of Phosphoenolpyruvate (PEP) to Pyruvate with concomitant production of ATP. It consists of four isoforms in mammals, which are tissue-specific PKL, PKR, PKM1, and PKM2. PKL, PKR, and PKM1 exist as stable tetramers, whereas PKM2 subunits form tetramers and dimmers. M2 isoform of Pyruvate Kinase (PKM2) is a crucial regulator and has the unique ability to shift glucose metabolism in favor of cancer cells. In accordance, cancerous state is correlated with high PKM2 expression in a variety of tumor tissues. Besides a crucial metabolic role, a significant chunk of data has unraveled the role of PKM2 in gene transcription and its ability to act as protein kinase. Due to the soaring number of papers dealing with the role of PKM2 in tumorigenesis, it has gained enormous attention in recent past. The review deals with the metabolic role of pyruvate kinase M2 in normal cell versus cancerous cells, and its therapeutic relevance and future directions in the field are also discussed.